The Oil Supply Speed Effect on Flow-Heat Characteristics of Bearing - Baohu Han; Xingjun Ju; Lei Zhang; Kun Yang; Weixin Sun; Guanglong Zhang; Bo Song (Shock and Vibration)
Bearing is the core component of high-speed rotating machinery. However, the lubricating oil plays an important role in reducing the temperature and the collision between components. It can improve the performance of the bearing under high-speed rotation. Therefore, based on the theory of oil-air two-phase flow, this paper establishes a numerical analysis flow-heat model of ball bearing under different oil supply. At the same time, the vibration is calculated. The influence of internal oil-air field and thermal characteristics on vibration is analyzed. The results show that the volume of oil is not uniformly distributed in the bearing chamber. The oil gradually decreases from the outer ring to the inner ring. It is mainly concentrated on the oil-air inlet. With the increasing of oil supply speed, the temperature of the bearing decreases firstly and then increases, and there is an optimal oil supply speed. The inner ring vibration velocity is basically similar to the temperature trend. Meanwhile, the lowest temperature is mainly concentrated near the oil-air inlet. The maximum error between simulation results and experimental results is 11.37%. Finally, the reliability of the simulation analysis is verified by the temperature and vibration experiment. It provides some theoretical support for the optimization of oil-air lubrication parameters of angular contact ball bearings.